Key policy challenges and opportunities to improve care for people with mental health and substance use disorders : proceedings of a workshop - Graig, Laurene A. (The National Academies Press, 2020)
Behavioral health and substance use disorders affect approximately 20 percent of the U.S. population. Of those with a substance use disorder, approximately 60 percent also have a mental health disorder. Together, these disorders account for a substantial burden of disability, have been associated with an increased risk of morbidity and mortality from other chronic illnesses, and can be risk factors for incarceration, homelessness, and death by suicide. In addition, they can compromise a person's ability to seek out and afford health care and adhere to treatment recommendations. To explore data, policies, practices, and systems that affect the diagnosis and provision of care for mental health and substance use disorders, the Health and Medicine Division of the National Academies of Sciences, Engineering, and Medicine created the Forum on Mental Health and Substance Use Disorders. The forum activities are expected to advance the discussion and generate potential ideas on ways to address many of the most persistent problems in delivering mental health and substance use services. The inaugural workshop, held October 15-16, 2019, in Washington, DC, explored the key policy challenges that impede efforts to improve care for those individuals with mental health and substance use disorders. This publication summarizes the presentations and discussion of the workshop.
Keywords: Mental health services -- United States.; Mental health planning -- United States.; Mentally ill -- Patients -- United States.; Substance abuse -- Patients -- United States.; Medical policy -- United States.; Mental health services.; Mental illness.; Drug addiction.; Drug abuse.; Medical care.; Patient-centered health care.; Medical policy.; Mental Health Services; Mental Disorders; Substance-Related Disorders; Delivery of Health Care; Patient-Centered Care; Health Policy; United States; Patient Care; Services de santé mentale -- États-Unis.; Santé mentale -- Planification -- États-Unis.; Personnes vivant avec un trouble de santé mentale -- Patients -- États-Unis.; Polytoxicomanie -- Patients -- États-Unis.; Politique sanitaire -- États-Unis.; Services de santé mentale.; Maladies mentales.; Toxicomanie.; Prestation de soins.; Soins centrés sur le patient.; Politique sanitaire.; Soins médicaux.; mental disorders.; drug abuse.; drug addiction.; Patient-centered health care; Mental illness; Medical care; Drug addiction; Drug abuse; Medical policy; Mental health planning; Mental health services; Substance abuse -- Patients; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.